Effect of Cold Rolling and Flash Annealing on Microstructure and Mechanical Behaviour of Austenitic Manganese Steel (Fe-1.15C-13Mn) - Abdul Hanin Al Hakam; Faried Miftahur Ridlo; Rifqi Aulia Tanjung; Lia Amalia Damar; Permana Andi Paristiawan (BRIN Publishing (Penerbit BRIN), 2023)
Austenitic manganese steel (AMS) is widely used in the mineral and mining industry under high workload condition due to its remarkable work-hardening capacity under impact. However, AMS typically has an austenitic matrix with carbides precipitated resulting in low hardness and brittle properties, which impaired its wear performance. In this study, cold deformation followed by flash annealing were conducted to improve the mechanical behavior of AMS. The experimental was carried out by solution treatment (ST), cold rolling (CR) with deformation degrees of 10% and 20%, and flash annealing (FA) at 915°C with holding times of 90 and 150 seconds. The microstructure evolution and mechanical behavior were studied. The ST produced a completely austenitic microstructure which was free of carbide, resulting in a decrease in strength and hardness, as well as improved ductility. After cold deformation, both of strength and hardness were substantially improved, followed by loss in ductility. Optical microstructures reveal the formation of deformation twin (DT) and annealing twin (AT) after cold deformed. Higher intensity of DT results in AMS with considerable strength and hardness but decrease in ductility. After FA process, cold deformed structures undergo microstructural restoration, which manifests by recovery stage at 90 s and recrystallisation stage at 150 s annealing time. At the same FA time, higher degree of deformation led to increase the hardness, while at the same degree of strain, longer annealing time led to a decrease of hardness. Moreover, both of higher degree of strain and longer annealing time during flash annealing were contributed to grain refinement, even though did not affected to the increase of tensile and hardness. In addition, 20% cold rolling followed by 150 s annealing time (CR20FA150) could be considered as an effective method to obtain the most optimum combination of strength and ductility with finer grain.